Cone-shaped resonator-based highly efficient broadband metamaterial absorber - Kumar R.; Singh B.K.; Pandey P.C. (My University, 2025)
We propose a highly efficient, low-cost metamaterial absorber of nickel (Ni) metal-based cone-shaped resonators with a silicon dioxide dielectric layer (SiO2). The proposed absorber exhibits an average absorption of 97% for the transverse magnetic and transverse electric modes over the visible region simulated by CST software. The nickel-metal impedance coincides with the impedance of free space and makes the proposed design an effective broadband absorber in the visible region. The average absorption with different incidence angles obtains over 90%, showing the polarization angles’ independence. The average absorption spectra are also examined for the absorber with different noble metals. In addition, short-circuit current densities (Jsc) are calculated at different incidence angles for both modes under a global air mass of 1.5 (AM1.5). We have also plotted the J–V curve to obtain the values of the open-circuit voltage (Voc), Fill Factor, and conversion efficiency (η), whose values are 0.563 V, 81.86, and 11.68%, respectively. The proposed metamaterial absorber can be utilized to develop more reliable, highly efficient, cost-effective, and maximum-power extraction photovoltaic systems. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.